ACUTE RESPIRATORY DISTRESS SYNDROME DAN ACUTE PNEUMONIA PADA NEAR DROWNING:SEBUAH LAPORAN KASUS - Prinka Adyana, Michelle (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana)
Near drowning is a condition in which the victim survived the first 24 hours. The World Health Organization ( WHO ) , recorded worldwide in 2000 there were 400,000 incident drowned accidentally . That is, this figure ranks second only to traffic accidents. Aspiration pneumonia is a complication of near drwoning which occurred in 80 % of cases of near drowning, while 50 % of patients sink into acute respiratory distress syndrome ( ARDS ) . This case report discusses the acute respiratory distress syndrome and acute pneumonia in near drowning 24 years old , who had drowned at the beach for ± 15 minutes , the chest x - ray obtained pulmonary edema dd / lung pnuemonia there pneuomothorax . Examination of multislice spiral computed tomography ( MSCT ) bilateral pneumothorax Thorax obtained major and minor fisuura right and left major fissure , pneumomediastinum , pulmonary pneumonia contusio / suspected aspiration pneumonia , emphysema subcutis . In intensive care patients conducted for 9 days and return to akitivitas everyday
Keywords: Near drowning, acute respiratory distress syndrome, acute pneumonia